Effects of bean seed size on bean plant performance - J. Marcos, J. Marcos; Avancine, F. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of bean seed size on germination, vigor and yield of bean plant (Phaseolus vulgaris L) cv. Aroana and Carioca were studied under laboratory and field conditions. The seeds were sized into classes differing by 0.4 mm in thickness. Physiological quality of seeds from size classes was evaluated using standard germination and vigor tests (first counting, speed of germination and accelerated aging test), during six months. The results showed that seed of the mean and larger size classes were better in physiological quality than those of smallest classes.
Keywords: Phaseolus vulgaris L.; germination; vigor; yield